Seasonal Dynamics of Soil Respiration in an Alpine Meadow: In Situ Monitoring of Freeze–Thaw Cycle Responses on the Qinghai–Tibet Plateau - Pei Wang; Chunqiu Li (Land, 2025)
Understanding the dynamics of soil respiration (Rs) in response to freeze–thaw cycles is crucial due to permafrost degradation on the Qinghai–Tibet Plateau (QTP). We conducted continuous in situ observations of Rs using an Li-8150 automated soil CO2 flux system, categorizing the freeze–thaw cycle into four stages: completely thawed (CT), autumn freeze–thaw (AFT), completely frozen (CF), and spring freeze–thaw (SFT). Our results revealed distinct differences in Rs magnitudes, diurnal patterns, and controlling factors across these stages, attributed to varying thermal regimes. The mean Rs values were as follows: 2.51 (1.10) μmol·m−2·s−1 (CT), 0.37 (0.04) μmol·m−2·s−1 (AFT), 0.19 (0.06) μmol·m−2·s−1 (CF), and 0.68 (0.19) μmol·m−2·s−1 (SFT). Cumulatively, the Rs contributions to annual totals were 89.32% (CT), 0.79% (AFT), 5.01% (CF), and 4.88% (SFT). Notably, the temperature sensitivity (Q10) value during SFT was 2.79 times greater than that in CT (4.63), underscoring the significance of CO2 emissions during spring warming. Soil temperature was the primary driver of Rs in the CT stage, while soil moisture at 5 cm depth and solar radiation significantly influenced Rs during SFT. Our findings suggest that global warming will alter seasonal Rs patterns as freeze–thaw phases evolve, emphasizing the need to monitor CO2 emissions from alpine meadow ecosystems during spring.